IMPROVING THE PROFESSIONAL COMMUNICATIVE COMPETENCE OF PHYSICS STUDENTS IN ENGLISH: PROBLEMS, SOLUTIONS, AND EMPIRICAL RESULTS - Xolmatova Maxbubaxon Axmadjon qizi (Western European Studies, 2026)
This article investigates the key problems associated with developing professional communicative competence (PCC) in English among undergraduate physics students and proposes scientifically grounded pedagogical solutions. Based on communicative competence theory, CLIL, ESP, and modular-credit technology, the study integrates linguistic, methodological, and subject-specific approaches. The research combines theoretical analysis with empirical data obtained from an experimental teaching program implemented at a higher education institution. Quantitative and qualitative results demonstrate a statistically significant improvement in students’ professional communication skills in English
Keywords: professional communicative competence; physics students; English for Specific Purposes